Mobile Learning Readiness of Junior High School Students in Science Learning - Anggi Datiatur Rahmat; Heru Kuswanto; Insih Wilujeng (JTP - Jurnal Teknologi Pendidikan, 2023)
Technology advancements and an increasing number of mobile phone owners among junior high school students have opened opportunities for teachers to integrate technology into the learning process, especially in science learning. Before implementing mobile learning in the classroom, researchers must assess whether students are ready to adopt the technology. Adding the perspective of junior high school students in West Java, the research aims to present a quantitative survey on students' mobile learning readiness. An online questionnaire survey was used to collect data in this study. The results shown that students can use mobile learning in science learning. Almost all students have mobile phones to support mobile science learning. However, some students are still worried about the problem of costs when learning using mobile because it requires internet access. Nevertheless, students agreed to know more about mobile learning. These findings can serve as a reference point for further studies if mobile science learning is widely used in junior high schools.